Religious Freedom and Multicultural Coexistence: A Qualitative Study of Students' Lived Experiences at Halu Oleo University, Kendari - Hasniah Hasniah; Yuyun Hendrawati; Abdul Rahman; Rayhan Hadiansah (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2026)
Background: Kendari is home to a diverse array of indigenous ethnic communities—including the Tolaki, Muna, Buton, and Konawe peoples—alongside migrant populations from across the archipelago, the city exhibits a complex mosaic of cultural and religious identities. Halu Oleo University (UHO), as the leading public university in the region, aggregates this diversity within its student body, creating a microcosm of broader Indonesian multiculturalism. Objectives: This study examines the lived experiences of religious freedom and multicultural coexistence among students at Halu Oleo University (UHO), Kendari, Southeast Sulawesi, Indonesia. Method: Employing a qualitative approach with in-depth interview methods, this research explores how university students perceive, navigate, and negotiate religious diversity in their daily social environments. Data were collected through semi-structured interviews with eight student informants representing diverse academic disciplines within the Faculty of Cultural Sciences. Result: The findings reveal that while students generally uphold mutual respect and tolerance as core values in everyday interactions, several structural and cultural tensions persist—including the dominance of majority religious practices, procedural barriers to house-of-worship construction, and the amplifying role of social media in religious tensions. Students consistently identified community dialogue, traditional leaders' mediation, and local cultural values such as gotong royong (communal cooperation) as key mechanisms for sustaining harmony. Conclusion: This research contributes to broader understandings of multiculturalism in Indonesian higher education contexts and highlights the need for more inclusive policy frameworks to protect religious minority rights. Keywords: religious freedom, multiculturalism, coexistence, Indonesian university students